Exodus - Matti, Erik (Imus Production, 2005)
In a world ravaged by war, mankind's fate rests on the reluctant shoulders of one man, Exodus, a grim, unsmiling mercenary with extraordinary fighting skills and a murky past. It is Exodus who leads the surviving humans against, the fearsome creatures of the dark, including Haring Bagulbol, an all-powerful being who is bent on human kind's annihilations.